The occurrence and impact of red mite (Dermanyssus gallinae) infestations in budgerigars (Melopsittacus undulatus) in Kashan (central parts of Iran) - Hajipour, Nasser; Ghorani, Mohammadreza; Ghorbiani , Mohsen; Shahbazfar , Amir Ali (Journal of Poultry Sciences and Avian Diseases, 2025)
The red mite of poultry, Dermanyssus gallinae, is the most significant blood-sucking ectoparasite affecting birds. This study aimed to document the infestation of Dermanyssus gallinae in budgerigars (Melopsittacus undulatus) and examine its pathological effects in Kashan (central Iran). Samples were taken from 150 birds, with skin samples fixed in 10% buffered formalin and histological sections prepared using standard Hematoxylin & Eosin staining techniques. The results indicated that 120 out of 150 budgerigars (80%) were infested with at least one mite, and Dermanyssus gallinae was found in most of the sampled nests. Pathological findings included hyperplastic epidermis, heterophilic inflammation of the skin, and severe hemorrhage in the dermis. The mite can be transmitted from budgerigars to other poultry and humans. In order to control the mite population while minimizing the harmful effects of acaricides on birds, it is recommended to spray acaricides twice a year, before and after nesting.